The relationship between self-efficacy and mental health among teachers' sample at al-Batinah North governorate the Sultanate of Oman = فاعلية الذات وعلاقتها بالصحة النفسية لدى عينة من معلمي محافظة الباطنة شمال بسلطنة عمان - Nasser AL Ghdani, Khalid Hamed; Ismail, Nik Ahmad Hisham (International Organization Center of Academic Research (OCERINT), 2020)
This quantitative study discussed the relationship between self-efficacy and mental health among a sample of teachers from Al-Batinah north Governorate, at the Sultanate of Oman. The problem in the self- efficacy, which has become an important and vital requirement in the teachers' personality, in facing the challenges of rapid and successive developments, and to enable them to acquire the necessary skills in dealing with students and their daily problems. So, the study aims to determine the level of both self-efficacy and mental health, the correlation between them, and individual differences in the teachers' variables. The study followed the descriptive analytical method. A random sample of (100) teachers was selected. The study used the Self-Efficiency Scale (Abu Ghaly, 2012) consisting of (30) statements and the mental health scale (Ismail, 2016) consisting of ( 36) statements. The findings indicated that: the level of self-efficacy among the teachers was an intermediate level (60.63%), the percentage of the level of mental health among the teachers reached (62.02%) which is also an intermediate level. The Pearson correlation coefficient between self-efficacy and mental health was equal to (0.68), which is a positive correlation coefficient, which means that the relationship is direct, that is, the more self-efficacy increases, mental health increases. It concluded that there are no statistically significant differences for teachers in the level of self-efficacy and mental health attributable to the variables . **************************************************************************** ناقشت هذه الدراسة الكمية العلاقة بين فاعلية الذات والصحة النفسية لدى عينة من معلمي محافظة الباطنة شمال بسلطنة عمان. تكمن المشكلة في فاعلية الذات التي أصبحت مطلباً مهماً وحيوياً في شخصية المعلم، لمساعدته على مواجهة متطلبات وتحديات التطورات المتسارعة والمتلاحقة، ولتمكينه من اكتساب المهارات اللازمة في التعامل مع الطلاب ومشكلاتهم اليومية. لذا تهدف الدراسة لتحديد مستوى كل من فاعلية الذات والصحة النفسية، والعلاقة الارتباطية بينهما، والفروق الفردية في المتغيرات للمعلمين. اتبعت الدراسة المنهج الوصفي التحليلي. تكون مجتمع الدراسة من جميع المعلمين العاملين في مدارس المحافظة، تم اختيار عينة عشوائية بلغت (100) معلم، استخدمت الدراسة مقياس فاعلية الذات (أبو غالي، 2012) المكون من (30) عبارة، ومقياس الصحة النفسية (إسماعيل، 2016) المكون من (36) عبارة. أشارت نتائج الدراسة: أن نسبة مستوى فاعلية الذات لدى معلمي المرحلة الأساسية العليا بلغت (60.63%) وهو مستوى متوسط، وأن نسبة مستوى الصحة النفسية لدى معلمي المرحلة الأساسية العليا بلغت (62.02%) وهو مستوى متوسط أيضاً. كما أشارت أن معامل الارتباط بيرسون بين فاعلية الذات والصحة النفسية يساوي (0.68) وهو معامل ارتباط إيجابي؛ مما يعني أن العلاقة طردية أي أنه كلما زادت فاعلية الذات زادت الصحة النفسية. وتوصلت أنه لا توجد فروق ذات دلالة إحصائية لدى المعلمين في مستوى فاعلية الذات والصحة النفسية تعزى للمتغيرات